Size-dependent impact of polystyrene microplastics on the toxicity of cadmium through altering neutrophil expression and metabolic regulation in zebrafish larvae. (15th December 2021) - Qin, Li; Duan, Zhenghua; Cheng, Haodong; Wang, Yudi; Zhang, Haihong; Zhu, Zhe; Wang, Lei
Abstract: Insufficient evidence exists regarding the visible physiological toxic endpoints of MPs exposures on zebrafish larvae due to their small sizes. Herein, the impacts of micro-polystyrene particles (μ-PS) and 100 nm polystyrene particles (n-PS) on the toxicity of cadmium (Cd) through altering neutrophil expressions were identified and quantified in the transgenic zebrafish ( Danio rerio ) larvae Tg(lyz:DsRed2), and the effects were size-dependent. When exposed together with μ-PS, the amount of neutrophils in Cd treated zebrafish larvae decreased by 25.56% through reducing Cd content in the larvae. By contrast, although n-PS exposure caused lower Cd content in the larvae, the expression of neutrophils under their combined exposure remained high. The mechanism of immune toxicity was analyzed based on the results of metabonomics. n-PS induced high oxidative stress in the larvae, which promoted taurine metabolism and unsaturated fatty biosynthesis in n-PS + Cd treatment. This observation was accordance with the significant inhibition of the activities of superoxide dismutase and catalase enzymes detected in their combined treatment. Moreover, n-PS promoted the metabolic pathways of catabolic processes, amino acid metabolism, purine metabolism, and steroid hormone biosynthesis in Cd treated zebrafish larvae. Nanoplasctis widely coexist with other pollutants in the environment at relatively low concentrations. We conclude that more bio-markers of immune impact should be explored to identify their toxicological mechanisms and mitigate the effects on the environment. Graphical abstract: Image 1 Highlights: The combined immune impacts of PS particles with Cd were size-dependent. Nano PS did not result in the decrease of neutrophils in Cd treated zerafish larvae. Nano PS induced Steroid hormone and Purine metabolism in Cd treated larvae. Transgenic zebrafish were sensitive in toxicity response of PS plastics at low dose.